2019
DOI: 10.11604/pamj.2019.33.99.16960
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of brucellosis and risk factors associated with its seropositivity in cattle, goats and humans in Iganga District, Uganda

Abstract: Introduction The burden of brucellosis among smallholder farmers is poorly-documented in Uganda. The disease burden is likely to be high, given the high levels of endemicity, lots of exposures and due to lack of control measures. In order to designate appropriate control measures, the magnitude and risk factors for brucellosis need to be known. We established the burden of and risk factors for Brucella seropositivity in cattle, goats, and humans in Iganga district, easte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 29 publications
3
18
3
Order By: Relevance
“…[11,15] In contrast, similar studies in South Sudan and Uganda found seroprevalences of 33.3% and 4.4% among cattle herders and livestock farmers respectively. [14,27] These findings were higher than those from our study in all occupational groups except for the study among slaughterhouse workers in Ghana. [15] Brucellosis has also been reported in butcher and slaughterhouse workers in Iran at 7.9% seroprevalence.…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…[11,15] In contrast, similar studies in South Sudan and Uganda found seroprevalences of 33.3% and 4.4% among cattle herders and livestock farmers respectively. [14,27] These findings were higher than those from our study in all occupational groups except for the study among slaughterhouse workers in Ghana. [15] Brucellosis has also been reported in butcher and slaughterhouse workers in Iran at 7.9% seroprevalence.…”
Section: Resultscontrasting
confidence: 78%
“…Some studies have reported human brucellosis at seroprevalences ranging from 0.02% to 33.3% in Zambia, Nigeria, Ghana, Cameroon, Sudan and Ethiopia. [9][10][11][12][13][14][15] In Tanzania, several studies have been done in Katavi, Manyara, Morogoro, Northern Tanzania, Mwanza and Tanga regions which have reported human brucellosis at seroprevalences ranging from 0.6 to 48.4%. [16][17][18][19][20][21][22][23] However, there is no previous report on the disease among the high-risk human population in Mbeya region.…”
Section: Introductionmentioning
confidence: 99%
“…Human brucellosis was also reported in recent brucellosis studies in Uganda published from 2010 to 2019. The reported human brucellosis prevalence varied between 4.0% and 33.0% (Ezama et al., 2018, 2019; Frank et al., 2017; Kansiime et al., 2015; Majalija et al., 2018; Migisha et al., 2018; Miller et al., 2016; Muloki et al., 2018; Nabukenya et al., 2013; Nanfuka, 2018; Nasinyama et al., 2014; Nguna et al., 2019; Tumwine et al., 2015). These human brucellosis results should, however, be interpreted considering that most of them were conducted on suspected patients attending hospitals with febrile illness or having prolonged fevers and on exposed cattle keepers and farm attendants in pastoralist and agro‐pastoralist communities.…”
Section: Resultsmentioning
confidence: 99%
“…seroprevalence rates than sheep and goats. It has been found that the prevalence of brucellosis is higher in pastoral grazing areas than in the urban and peri-urban areas [ 32 ]. In the present study, sheep and goats were originally from urban and peri-urban areas of Afgoye and Jowhar districts, which may explain the lower Brucella seroprevalence found.…”
Section: Discussionmentioning
confidence: 99%